Case Report: Revisiting the Internal Mammary Artery Perforator Flap: Salvage Option for Circumferential Pharyngo-Esophageal Defects - Marsden, Nicholas; Shukla, Lipi; Grinsell, Damien (Frontiers in Surgery, 2021)
Patients that present with pharyngeal strictures and pharyngocutaneous fistulas in the context of previous reconstruction and post-operative radiotherapy often report significant morbidity and reduction in quality of life. Reconstruction of such defects present a substantial clinical challenge requiring the importation of unirradiated vascularized tissue to facilitate healing in a friable, fibrotic and vessel depleted tissue bed. The authors present a case report demonstrating an adaptation of the internal mammary artery perforator (IMAP) flap for reliable reconstruction of circumferential pharyngeal defects with primary tension free closure of the donor site. This technique avoids the use of free tissue transfer in a hostile, irradiated neck. The tubed IMAP flap is an excellent option, serving the purposes of reconstruction as well as addressing the patient’s presenting issues of a chronic sinus and pharyngeal stricture inhibiting oral intake.